2023
DOI: 10.3390/admsci13010024
|View full text |Cite
|
Sign up to set email alerts
|

“Searching for Gold” with Sustainable Human Resources Management and Internal Communication: Evaluating the Mediating Role of Employer Attractiveness for Explaining Turnover Intention and Performance

Abstract: Objective: The main objective of this study is to evaluate the impact of sustainable human resources management (SHRM) and internal communication (IC) on turnover intention (TI) and employee performance (PER) while assessing the mediating role of organizational attractiveness (AT) over these relationships. In this sense, this study intends to evaluate the effect of SHRM and IC on employee PER and TI, with AT acting as the mediator in a joint model of analysis. Methodology: To achieve the aforementioned purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…Therefore, this study is in line with other studies previously conducted that found a relationship between symmetric internal communication and organizational identification (Sun et al 2021;Yue et al 2021). It can also be found that adopting practices geared towards good internal communication can improve employee performance in the organization (Ahmed and Rafiq 2002;Latham et al 2002;Gomes et al 2021Gomes et al , 2023.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, this study is in line with other studies previously conducted that found a relationship between symmetric internal communication and organizational identification (Sun et al 2021;Yue et al 2021). It can also be found that adopting practices geared towards good internal communication can improve employee performance in the organization (Ahmed and Rafiq 2002;Latham et al 2002;Gomes et al 2021Gomes et al , 2023.…”
Section: Discussionsupporting
confidence: 91%
“…The study results show that one of the key elements of organizational communication is ensuring that the employees are informed in due time in relation to the tasks that need to be completed, i.e., ensuring transparent institutional communication. The provision of information to employees in due time through internal channels contributes to a higher performance by employees (Gomes et al 2023). Polycarp (2022) showed a link between internal communication and employee performance.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have looked into the link between internal communication and employee performance. The way in which an organization provides information to its employees and manages its internal communication channels may positively influence employee performance (Gomes et al 2023). Polycarp (2022) presented evidence on the existence of a positive relation between employee performance and internal communication.…”
Section: Organizational Communicationmentioning
confidence: 99%
“…Based on social identity theory, employees who identify their firms’ values, will modify their work values toward the firms’ values, which will form a green commitment. However, if employees cannot modify their work value to meet their firms’ values, they will leave their firms [ 26 , 27 , 28 , 29 ], which will not form a green commitment.…”
Section: Literature Reviewmentioning
confidence: 99%